(untitled) (IUBAT Review, 2026)
This study assessed the treatment efficiency of the physical, chemical, and biological treatment processes to treat effluent discharged for a pharmaceutical factory. The treatment mechanism comprised of equalization tank, neutralization tank, anaerobic followed by aerobic bioreactors, two stage clarification system, reed bed bio-filtration process, and post aeration system. The effluent quality parameters such as pH, turbidity, TDS, TSS, TS, COD and BOD5 were analyzed in the laboratory with standard methods. The overall pollution removal efficiencies were 100% for turbidity, 97% for TSS, 95% for COD, and 97% for BOD5. The average reduction ranges of Turbidity, TSS, TS, COD and BOD5 were 201 FTU to 0 FTU, 512 mg/l to 13 mg/l, 912 mg/l to 530 mg/l, 2034 mg/l to 99 mg/l, and 1126 mg/l to 29 mg/l respectively were observed in the final stage. In terms of performance evaluation of individual treatment units, the anaerobic treatment unit achieved 1%, 17%, and 37% removal efficiencies for turbidity, COD, and BOD5 respectively; while the aerobic unit achieved 76%, 86%, and 86% removal efficiencies for the same parameters. The chemical treatment process was found effective for TSS and turbidity removal purpose. The Reed Bed performed well in removing BOD5, COD, and Turbidity. IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 264-282